2018
DOI: 10.14738/abr.65.4540
|View full text |Cite
|
Sign up to set email alerts
|

FDI And Economic Growth Relationship In Sub-Saharan Africa: Is The Domestic Financial System A Significant Intermediator?

Abstract: This paper contributes to the literature on the effect of Foreign Direct Investment (FDI) on economic growth by examining the role of financial development as a source of absorptive capacity in the FDI-economic growth relationship in Sub-Saharan Africa (SSA). Using panel data econometric techniques and an unbalanced dataset of 1989-2013, we examine the independent effect of FDI on economic growth, as well as the impact of an interactive relationship between FDI and financial development on economic growth in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…Consistent with the earlier studies (Ehigiamusoe et al, 2019; Gazdar & Cherif, 2015; Hermes & Lensink, 2003; Moradbeigi & Law, 2017; Olagbaju & Akinlo, 2018; Olaniyi & Adedokun, 2020; Olaniyi & Oladeji, 2020; Saidi, 2020), the interactive term in Equation ) gives room to examine the moderating role of institutional quality in influencing the role of financial development in economic growth process of Kenya. From Equation ), the marginal benefits of financial development on growth is determined by finding the partial derivative of the Equation with respect to financial development as follows rgdpctfdt=δ2+δ4instt …”
Section: Methodssupporting
confidence: 70%
“…Consistent with the earlier studies (Ehigiamusoe et al, 2019; Gazdar & Cherif, 2015; Hermes & Lensink, 2003; Moradbeigi & Law, 2017; Olagbaju & Akinlo, 2018; Olaniyi & Adedokun, 2020; Olaniyi & Oladeji, 2020; Saidi, 2020), the interactive term in Equation ) gives room to examine the moderating role of institutional quality in influencing the role of financial development in economic growth process of Kenya. From Equation ), the marginal benefits of financial development on growth is determined by finding the partial derivative of the Equation with respect to financial development as follows rgdpctfdt=δ2+δ4instt …”
Section: Methodssupporting
confidence: 70%
“…The path-breaking Harrod-Domar model (1939, 1946 remains the fundamental reference in the economics of investment, and it highlights the significance of determining the rate of investment, needed to achieve a certain rate of economic growth (Evans, 2018). In the same vein, the role of foreign investment (in the form of FDI) in economic growth has been recognized as key in the literature (See Gunby, Jin and Reed, 2017;Olagbaju and Akinlo, 2018;Bunte et al, 2018;Sharma, Rishad and Gupta, 2018). However, this role of FDI in economic growth is highly controversial.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Olagbaju and Akinlo (2018), for example, found that FDI can be growth-enhancing for Sub-Saharan Africa (SSA) countries only if there is a developed financial system. They also demonstrated that the causal relationship between financial system development and FDI is stronger for low-income countries as compared to middle-income countries in SSA.…”
Section: Brief Literature Reviewmentioning
confidence: 99%